Setaria viridis as a model for translational genetic studies of jasmonic acid-related insect defenses in Zea mays. (February 2020) - Hunter, Charles T; Block, Anna K; Christensen, Shawn A; Li, Qin-Bao; Rering, Caitlin; Alborn, Hans T
Highlights: Genetic similarity between setaria and maize allows functional genetic studies in setaria to be translated to maize. Core jasmonic acid-dependent metabolic and transcriptional responses are similar between setaria and maize. Secondary metabolite production tends to be species specific, limiting the translational genetic studies for some pathways. Setaria does not produce 12-OPDA, benzoxazinoids, green-leaf volatiles, and numerous terpenoid volatiles found in maize. Abstract: Little is known regarding insect defense pathways in Setaria viridis (setaria), a model system for panicoid grasses, including Zea mays (maize). It is thus of interest to compare insect herbivory responses of setaria and maize. Here we use metabolic, phylogenetic, and gene expression analyses to measure a subset of jasmonic acid (JA)-related defense responses to leaf-chewing caterpillars. Phylogenetic comparisons of known defense-related maize genes were used to identify putative orthologs in setaria, and candidates were tested by quantitative PCR to determine transcriptional responses to insect challenge. Our findings show that while much of the core JA-related metabolic and genetic responses appear conserved between setaria and maize, production of downstream secondary metabolites such as benzoxazinoids and herbivore-induced plant volatiles are dissimilar. This diversity of chemical defenses and gene families involved in secondary metabolism among grasses presents new opportunities for cross species engineering. The high degree of genetic similarity and ease of orthologous gene identification between setaria and maize make setaria an excellent species for translational genetic studies, but the species specificity of downstream insect defense chemistry makes some pathways unamenable to cross-species comparisons.